2022
DOI: 10.1002/anie.202203063
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Photocatalytic CO2 Methanation with Water Vapor on Single‐Atom Platinum‐Decorated Defective Carbon Nitride

Abstract: Solar‐driven CO2 methanation with water is an important route to simultaneously address carbon neutrality and produce fuels. It is challenging to achieve high selectivity in CO2 methanation due to competing reactions. Nonetheless, aspects of the catalyst design can be controlled with meaningful effects on the catalytic outcomes. We report highly selective CO2 methanation with water vapor using a photocatalyst that integrates polymeric carbon nitride (CN) with single Pt atoms. As revealed by experimental charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 56 publications
0
65
0
Order By: Relevance
“…In the FTIR spectrum of P25/Pt (Figure 5b), several new peaks emerged. The peaks at 1108 and 1165 cm À 1 were associated with CHO* and CH 3 O*, [2,41] respectively. Both groups were important intermediates in the conversion of CO 2 to CH 4 .…”
Section: Chemistry-a European Journalmentioning
confidence: 98%
“…In the FTIR spectrum of P25/Pt (Figure 5b), several new peaks emerged. The peaks at 1108 and 1165 cm À 1 were associated with CHO* and CH 3 O*, [2,41] respectively. Both groups were important intermediates in the conversion of CO 2 to CH 4 .…”
Section: Chemistry-a European Journalmentioning
confidence: 98%
“…The dicoordinated N atoms in tri‐s‐triazine motifs substituted by the O atoms lead to enhance the separation efficiency of photo‐generated charge carriers of CN and then promote the reaction [4a] . Recently, single‐atom catalysts have become a hot topic in the field of materials due to their abundant and well‐defined atomic sites for tuning the electronic structure of catalysts [4b–o] . The combination of single‐atom with semiconductor (e.g., CN) offers new opportunities to solve long‐term problems in the field of photocatalysis [4g–j] .…”
Section: Introductionmentioning
confidence: 99%
“…Xiong and co‐workers found that high photocatalytic CO 2 methanation can be achieved by integrating defective CN with single Pt atoms. Mechanism studies demonstrated that the single Pt sites, carbon nitride defect and the neighbored −OH groups are responsible for achieving high CH 4 selectivity [4m] . However, the reported CN based materials still suffer from the insufficient catalytic sites and limited charge separation ability, restricting the further practical application in photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Energy and climate solutions aiming at carbon neutrality are new requirements for future sustainable development, and the conversion of CO 2 into high-value energy substances is an effective way to achieve this goal, alleviating or even solving environmental pollution and energy crises ( Gil and Bernardo, 2020 ; Zhang et al, 2022 ). As a clean and efficient carbon-based fuel, methane (CH 4 ) is considered an effective tool to realize CO 2 resource utilization, providing a strategy for the development of new energy ( Shi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%